Treatment With Vasopressor Agents for Cardiovascular Shock Patients With Poor Renal Function; Results From the Japanese Circulation Society Cardiovascular Shock Registry - Yagi, Tsukasa; Nagao, Ken; Tachibana, Eizo; Yonemoto, Naohiro; Sakamoto, Kazuo; Ueki, Yasushi; Imamura, Hiroshi; Miyamoto, Takamichi; Takahashi, Hiroshi; Hanada, Hiroyuki; Chiba, Nobutaka; Tani, Shigemasa; et al. (Frontiers in Medicine, 2021)
According to the guidelines for cardiogenic shock, norepinephrine is associated with fewer arrhythmias than dopamine and may be the better first-line vasopressor agent. This study aimed to evaluate the utility of norepinephrine versus dopamine as first-line vasopressor agent for cardiovascular shock depending on the presence and severity of renal dysfunction at hospitalization. This was a secondary analysis of the prospective, multicenter Japanese Circulation Society Cardiovascular Shock Registry (JCS Shock Registry) conducted between 2012 and 2014, which included patients with shock complicating emergency cardiovascular disease at hospital arrival. The analysis included 240 adult patients treated with norepinephrine alone (n = 98) or dopamine alone (n = 142) as the first-line vasopressor agent. Primary endpoint was mortality at 30 days after hospital arrival. The two groups had similar baseline characteristics, including estimated glomerular filtration rate (eGFR), and similar 30-day mortality rates. The analysis of the relationship between 30-day mortality rate after hospital arrival and vasopressor agent used in patients categorized according to the eGFR-based chronic kidney disease classification revealed that norepinephrine as the first-line vasopressor agent might be associated with better prognosis of cardiovascular shock in patients with mildly compromised renal function at admission (0.0% vs. 22.6%; P = 0.010) and that dopamine as the first-line vasopressor agent might be beneficial for cardiovascular shock in patients with severely compromised renal function (odds ratio; 0.22 (95% confidence interval 0.05–0.88; P = 0.032)). Choice of first-line vasopressor agent should be based on renal function at hospital arrival for patients in cardiovascular shock. Clinical Trial Registration URL: http://www.umin.ac.jp/ctr/. Unique identifier: 000008441